Science teachers' knowledge of school-based assessment / Majorie Awang - Awang, Majorie (2014)
In 2011, school-based assessment (SBA, hereafter) was introduced into Malaysian public schools to enhance the assessment system. As key players in the teaching and learning process, teachers are required to equip themselves with good knowledge and understanding of assessment including SBA. Therefore, this study investigated the Science teachers' knowledge and understanding of assessment and the implementation of SBA in Malaysian Secondary Science classrooms. It also investigated the benefits of SBA and the challenges faced by teachers. The study involved a total of 66 lower secondary science teachers teaching at 6 secondary schools located in the district of Sri Aman in Sarawak. Data was collected using a questionnaire and semi-structured interviews with 6 teachers. The results obtained indicated that teachers possessed sufficient and a moderate level of knowledge and understanding of SBA in terms of definition and terminology of SBA and the implementation of SBA at the planning administering and scoring stage of assessment. However, teachers possessed limited knowledge with regards to general rules of assessment. Inferential statistics conducted using the independent-samples t-test further showed that Science teachers' overall knowledge and understanding of SBA is not influenced by gender, school locality or experience. Nevertheless, there was a significant difference in the knowledge and understanding of SBA in terms of definition, terminology and general rules of SBA between novice and experienced teachers. The experienced teachers also have a significantly better and higher level of knowledge on scoring and reporting SBA scores. Teachers also highlighted that SBA has actually helped them to improve on the student's learning and the teacher's competencies. Nevertheless the teachers stressed that SBA increased teacher's workload and they felt that time constraint was one of their major concerns. Taking into consideration these findings, and aligning them with the initiatives of the National Educational Blueprint, (NEB), teachers must be provided with sufficient training in general assessment. They must also be provided continuous professional development (CPD) so that they can be better informed and motivated to see the many benefits of SBA. Such a move could see a more effective implementation of SBA.